Vacuum Air-lift Bioreactor for Microalgae Production - G. Marotta (Chemical Engineering Transactions, 2017)
Microalgae production is receiving an increasing interest both by research institutions and commercial companies (Di Caprio et al., 2016). This is due to the growing consciousness of the need to move towards renewable, sustainable feedstoks for commodities production (Wang et al., 2012). However, process development at industrial scale, either based on open or closed photobioreactors, still is in a rather early stage and there is room for further development (Morweiser et al., 2010), especially aimed at reducing process costs.